Co-influence of fermentation time and temperature on physicochemical properties, bioactive components and microstructure of ting (a Southern African food) from whole grain sorghum. (October 2018) - Adebo, Oluwafemi Ayodeji; Njobeh, Patrick Berka; Adebiyi, Janet Adeyinka; Kayitesi, Eugenie
Abstract: Fermentation parameters for ting production from whole grain sorghum were optimized and the pH, titratable acidity, total viable bacteria count, total lactic acid bacteria count, total fungal and yeast count, tannin content, total phenolic content, total flavonoid content and antioxidant activities were studied. Milled whole grain sorghum was mixed with an equal volume of water and spontaneously fermented to obtain ting samples. Values of all the parameters studied showed significant (p ≤ 0.05) changes with increased fermentation time and temperature. Using numerical multi-response optimization, optimal fermentation conditions of whole grain ting were estimated at 28 °C for 72 h and at these conditions, reduced pH (5.9), high titratable acidity (1.1 g/kg), good microbial growth accompanied with relatively high values of total phenolic content (46.1 mg GAE/g), total flavonoid content (40.9 mg CE/g) tannin content (14.1 mg CE/g) and antioxidant activity (3.7 µM TE/g) were obtained. Liquid chromatography-tandem mass spectrometry quantification of phenolic compounds showed that the optimal ting samples (fermented at 28 °C for 72 h) had comparable levels of catechin (12.4 µg/g), gallic acid (0.75 µg/g) and quercetin (0.61 µg/g) concentrations, to other ting samples. Scanning electron microscopy of ting samples showed no changes with fermentation. This study would help improve whole grain ting processing, which might increase the consumption of this potentially health promoting food. Highlights: Ting was obtained from whole grain sorghum. Numerical optimization was used to predict optimal fermentation conditions at 28 °C for 72 h. Tannin contributed to the antioxidant activities. Elevated fermentation time and temperature led to an increase in mean levels of some phenolic compounds.